PENGARUH PENERIMAAN PAJAK DAERAH DAN PENERIMAAN RETRIBUSI DAERAH TERHADAP BELANJA DAERAH - Sholeman, Muhammad; Yanti, Rizky Febri; Waruwu, Aurelia Siska Yanti; Manalu, Simon Patar Rizki; Pakpahan, Sevalina (Dinamika Akuntansi Keuangan dan Perbankan, 2024)
The purpose of this study was to determine the effect of local tax revenue and local retribution on local expenditure. The correlational method was used in this study. Multiple linear regression analysis was used as a data analysis technique in this study. Conclusions that can be drawn from this study: 1) local tax separately affects local expenditure; 2) local retribution separately does not affect local expenditure; 3) local tax and local retribution simultaneously affect local expenditure. To increase the capacity of local expenditure through local taxes and retribution, the following should be done: 1) expand the capacity of the local economy that can be taxed; 2) develop the capacity of MSMEs to contribute to generating local retribution; 3) balance the growth of local taxes with the growth of local retribution through the development of local economic capacity in order to increase the capacity of local spending.